Heavy Metals in Soils From Intense Industrial Areas in South China: Spatial Distribution, Source Apportionment, and Risk Assessment - Su, Chuanghong; Meng, Jing; Zhou, Yunqiao; Bi, Ran; Chen, Zhenwei; Diao, Jieyi; Huang, Zhangxun; Kan, Zhiyi; Wang, Tieyu (Frontiers in Environmental Science, 2022)
The pollution of heavy metals caught a lot of interest worldwide in recent years. In present study, 8 typical heavy metals were detected in 71 surface and 67 subsurface soils, collected near intense industrial activities in South China. Spatial distributions, sources apportionment, and risk were analyzed by using geographical information system, and combined approach including principal component analysis (PCA), positive matrix factorization (PMF) and geoaccumulation index. The concentrations of Cd, As, Hg, Cu, Ni, Pb, and Zn (except Cr) were higher than the corresponding local background level, while exhibited different pollution degrees in surface and subsurface soils. The PMF results showed that agriculture, industry, transportation and nature were the four main contributed sources of heavy metals in soils from the study area. Overall, anthropogenic activities were found to be the dominant factor and significantly influence on heavy metals in surface and subsurface soils. Health risks to the population through soil inhalation, skin contact and ingestion indicated that non-carcinogenic and carcinogenic risks of heavy metals in soil in the study area were unacceptable. Adults have a higher risk of cancer than children and the contribution of each exposure route is higher than that of children. Therefore, we should pay more attention to heavy metal pollutions in soils in economically developed areas such as the South China and other areas.